2018
DOI: 10.1016/j.phycom.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of partial phase decorrelation on the performance of pilot-assisted millimeter-wave RoF-OFDM systems

Abstract: It is well known that in radio over fiber (RoF) systems, the transmission performance of orthogonal frequency-division multiplexing (OFDM) is highly sensitive to phase noise. In these systems, the radio frequency (RF) signal is generated by beating a reference and a modulated signal at the base station and, therefore, the phase noise of the RF signal depends on the phase noise of both reference and modulated signals as well as on the correlation between them. In many RoF systems, the reference and modulated si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 49 publications
(66 reference statements)
0
20
0
Order By: Relevance
“…Note that all stages experimenting with the RoF-OFDM signal from the central station to a certain base station were explained in our previous work [9]. The authors in [23] revealed that in terms of the time delay parameter, the heterodyning field correlates perfectly (τ = 0), decorrelates partially (0 < τ < 1/∆ν), or decorrelates completely (τ > 1/∆ν).…”
Section: Orthogonal Frequency Division Multiplexing Radio Over Fiber mentioning
confidence: 88%
See 4 more Smart Citations
“…Note that all stages experimenting with the RoF-OFDM signal from the central station to a certain base station were explained in our previous work [9]. The authors in [23] revealed that in terms of the time delay parameter, the heterodyning field correlates perfectly (τ = 0), decorrelates partially (0 < τ < 1/∆ν), or decorrelates completely (τ > 1/∆ν).…”
Section: Orthogonal Frequency Division Multiplexing Radio Over Fiber mentioning
confidence: 88%
“…Depending on the subcarrier position, a symbol constellation takes the value of either the data symbol d k or the pilot symbol p k [20]. If the OFDM-based RoF system is characterized by correlated-phase fields at the central station (the direct optical detection approach), the input to the OFDM demodulator is corrupted by (i) phase noise due to laser linewidth, as well as chromatic dispersion [9] and (ii) AWGN due to thermal and shot noises [21]. After the photo detection and down-conversion processes, the RoF-OFDM signal may be written as [22]:…”
Section: Orthogonal Frequency Division Multiplexing Radio Over Fiber mentioning
confidence: 99%
See 3 more Smart Citations